Resource Valuation of Kalilingseng-Cave Manganese Mining Site as a Tourist Destination Using the Travel Cost Method - Suharyadi, Heru; Soewardi, Tiara Juniar; Frampton, Samatha Michelle; Afifah, Fadhilah; Christopher, Christopher (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Kalilingseng Cave, a former Dutch-era manganese mine in Kulon Progo, has untapped potential for educational and cultural tourism. Specific Background: Despite its historical and aesthetic value, the cave remains underdeveloped as a tourist site, lacking comprehensive economic valuation. Knowledge Gap: Prior research has not addressed the cave's economic potential as a tourism destination, leaving a gap in understanding its full value. Aims: This study aims to evaluate the tourism potential of Kalilingseng Cave using SWOT analysis and estimate its economic value through the Travel Cost Method (TCM). Results: The SWOT analysis highlights the cave’s accessibility and proximity to public facilities. TCM results show an average WTP of IDR 67,000.00, with annual economic benefits of IDR 21,775,000.00. Novelty: This research uniquely integrates SWOT and TCM to assess the tourism potential of an abandoned mining site. Implications: Proper development could make Kalilingseng Cave a sustainable tourist destination, benefiting the local economy and supporting geotourism education. Highlights: Tourism Potential: Kalilingseng Cave's historical and aesthetic value positions it as an educational and geotourism destination. Economic Valuation: The Travel Cost Method reveals an annual benefit of IDR 21,775,000.00 from visitors, indicating potential for community development. SWOT Insights: The SWOT analysis highlights strengths like accessibility and opportunities for geotourism while addressing weaknesses such as poor air circulation and lack of official management. Keywords: Ex-Manganense Mining, Kalilingseng, SWOT, Travel Cost Method